THE EFFECT OF NO AND O2 CONCENTRATION IN A THREE COMPONENT CO-NOO2 REACTION ON CATALYTIC SURFACE APPLYING THE PRECURSOR MECHANISM: A COMPUTER SIMULATION STUDY - Qaisrani, A. U.; Khalid, M. (The Nucleus, 2012)
We have studied a model for the three component CO-NO-O2 catalytic reaction on hexagonal surface through Monte Carlo simulations. This study is based on non-thermal process, which involves the precursor motion of CO molecule. The effect of ratio NO:O2 on the catalytic reduction of NO into N and O and oxidation of CO to CO2 are introduced. Many observations are recorded in the three component reaction. It is observed that with the inclusion of precursor mechanism with the Langmuir-Hinshelwood (LH) mechanism, the reactive window gets enhanced. The phase diagrams of the surface coverage with CO, N, O and the steady state production of CO2 and N2 are shown as a function of partial pressure of CO in the gas phase.